Contribution of street food to dietary intake of habitual urban consumers: A cross-sectional study in Kampala city, Uganda. Issue 3 (September 2020) - Sseguya, Wenceslaus; Matovu, Nicholas; Swann, Jessica; Draper, Alizon
Background: Street food has continued to be a popular food source in the urban settings of developing countries and is proving to be a vital urban dietary source. However, its dietary contribution among urban populations is yet to be comprehensively understood. Aim: To assess how street food contributes to the dietary intake of habitual street food consumers. Methods: We conducted a community-based cross-sectional study among habitual street food consumers in Kampala city. We defined habitual intake as consumption of a serving of any street food for ≥2 days/week regardless of the food group and number of times it was consumed in a particular day. Questionnaires were used to capture quantitative data on sociodemographic characteristics, anthropometry, 24-hour diet intake and 2-month street food consumption frequency. The Nutritics ® diet analysis software version 4.3 and STATA version 13.0 were used for nutrient and statistical analyses respectively. Results: Street food contributed considerably to the daily intake of fat (49.1%), sodium (38.4%) and calcium (36.5%) and least towards the daily intake of vitamin A (11.3%). The majority of consumers opted for street food at breakfast (50%) whereas lunch and snacks featured the least for overall street food inclusion (all 20%). Overall, men demonstrated more dietary intake and inclusion at meals from street food than women. Conclusions: This study indicates a significant contribution of street food for urban consumers but men derive more benefit than women in terms of nutrient intake and inclusion of street food in meals.